HUBUNGAN ANTARA UMUR DAN INTENSITAS CAHAYA LAS DENGAN KELELAHAN MATA PADA JURU LAS PT. X DI KABUPATEN GRESIK - Dedy Setiawan (Universitas Airlangga, 2016)
Welding occurs much hazard especially toward welders eyestrain. The Objective of study was to analyzed relation between age and eyestrain and also weld luminous intensity and eyestrain at welders of PT. X in District of Gresik. Research was carried out by cross sectional and observational study. Subjects were 20 welders of PT. X in District of Gresik. Data collecting was carried out by interview, measurement instrument, and examination. The independent variables were age and weld luminous intensity, and the dependent variable was eyestrain. Spearman Test was used to correlate between age and eyestrain. Pearson Product Moment Test was used to correlate between weld luminous intensity and eyestrain. According to the results, there was significant correlation between age and eyestrain (p = 0,007). There are more eyestrains will be occurred in older age. Result also showed that there was significant correlation between weld luminous intensity and eyestrain (p = 0,023). High exposure of weld luminous intensity will occurs contrast so that eyes needs much effort to adapt it. Light of weld contain UV light, visible light, and infrared radiation. In conclusion, there was significant correlation between age and eyestrain. And also, there was significant correlation between weld luminous intensity and eyestrain. Welders must use face shield depend on types of welding and company should held eyes examination to welders routinely.Keywords: age, weld luminous intensity, eyestrain